Audio-Visual Media Based on Canva to Support Online Learning in SD 3 Wergu Wetan - Fina Fakhriyah; Siti Masfuah; Muhammad Malik Hakim (Journal on Education, 2024)
Learning during the Covid-19 pandemic requires special and more intense attention for an educator, especially variations in the use of learning technology. The purpose of this activity is to assist teachers in the development of learning media based on the Canva application. The stages of this activity include the initial analysis stage (field conditions), introduction to the Canva application, identification of materials, and product preparation. The data obtained were then analyzed descriptively qualitatively. The product that has been developed by the SD 3 Wergu Wetan teacher is validated by an expert to see the suitability of the material content, level suitability, design completeness, media design feasibility, and attractiveness. Based on the results of expert validation, a score of 87.9 percent was obtained with a very suitable category for use. From the results of this validation, , it is used as a basis by the teacher to then carry out the recording stages of learning with the help of this Canva application and upload it to the youtube platform as a means of explaining material to support online learning to students at SD 3 Wergu Wetan.